2022
DOI: 10.1037/pha0000491
|View full text |Cite
|
Sign up to set email alerts
|

What influences demand for cigars among African American adult cigar smokers? Results from a hypothetical purchase task.

Abstract: African Americans (AA) have historically been targeted by the tobacco industry and have the highest rates of current cigar use among racial/ethnic groups in the U.S. Yet, there is limited evidence on other factors influencing cigar use. Amongst a sample of 78 AA current cigar (any type) smokers, log-linear regression models examined correlates of cigar demand obtained from a validated behavioral economic purchase task. Mean intensity, or cigar demand when free, was 6.68 cigars (standard deviation [SD]: 8.17), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This may impact the generality of the findings. Single-commodity drug-related purchase tasks have demonstrated utility across a range of diverse backgrounds (e.g., age, substance use disorder severity, ethnicity, race, veteran status, comorbid mental health disorders; Berey et al, 2022; Simuzingili et al, 2022; Zvorsky et al, 2019). Particularly for the current area of research, however, individual backgrounds and lived experience likely impact what kinds of activities function as substitutes and the feasibility of incorporating those activities into recovery efforts.…”
Section: Discussionmentioning
confidence: 99%
“…This may impact the generality of the findings. Single-commodity drug-related purchase tasks have demonstrated utility across a range of diverse backgrounds (e.g., age, substance use disorder severity, ethnicity, race, veteran status, comorbid mental health disorders; Berey et al, 2022; Simuzingili et al, 2022; Zvorsky et al, 2019). Particularly for the current area of research, however, individual backgrounds and lived experience likely impact what kinds of activities function as substitutes and the feasibility of incorporating those activities into recovery efforts.…”
Section: Discussionmentioning
confidence: 99%
“…This belief, coupled with a lack of understanding that cannabis is addictive and blunts also contain nicotine, may lead Black young adults to continue smoking blunts. Past research has suggested that cannabis use is associated with cigar addiction in Black cigar smokers [ 39 ]. Thus, as blunt smoking becomes an increasingly common way to consume cannabis, especially among Black young adults [ 40 ], it is imperative to inform people who predominantly smoke blunts about the harm and risk of developing not only cannabis use dependence and disorders but also nicotine addiction and its associated health consequences.…”
Section: Discussionmentioning
confidence: 99%